Analysis of Urea Levels in Chronic Kidney Disease Patients Based on Age, Sex, and Hemodialysis Frequency - Yoni Astuti (CV. Inara, 2026)
Introduction: Chronic kidney disease (CKD) is a progressive condition characterized by declining renal function and accumulation of metabolic waste such as urea. Hemodialysis is essential in advanced CKD to reduce urea levels, which serve as an important marker for renal function and dialysis adequacy. Variations in urea levels may be influenced by demographic factors such as age and sex, as well as treatment-related factors including hemodialysis frequency. Aims: This study aimed to analyze urea levels and hemodialysis frequency among CKD patients based on age groups (<50 years, 51–60 years, and ≥61 years) and sex. Methods: A descriptive quantitative study with a cross-sectional design was conducted using secondary data from medical records of CKD patients undergoing hemodialysis at PKU Muhammadiyah Gamping Hospital from 2021 to 2023. A total of 78 complete records were included. Urea levels and hemodialysis frequency were analyzed descriptively, and an independent t-test was used to assess differences between male and female patients. Results: Urea levels varied across age groups within each sex. In males, the highest mean urea level was observed in the 51–60 years group, while females showed a progressive increase with age. Male patients exhibited greater variability, especially in older age groups, whereas females showed more consistent patterns. Hemodialysis frequency remained relatively stable in males but increased with age in females. However, statistical analysis revealed no significant difference in urea levels between sexes (p = 0.919), with mean values of 99.35 mg/dL in males and 100.38 mg/dL in females. Conclusion: Urea levels in CKD patients vary according to age and demonstrate different patterns between sexes, but no significant sex-based differences were identified. These findings suggest that urea dynamics are influenced by multiple factors, highlighting the importance of individualized management strategies in CKD patients undergoing hemodialysis.